Neuropsychiatric symptoms in spinocerebellar ataxias and Friedreich ataxia - Karamazovova, Simona; Matuskova, Veronika; Ismail, Zahinoor; Vyhnalek, Martin (Neuroscience and biobehavioral reviews, 2023)
Apart from its role in motor coordination, the importance of the cerebellum in cognitive and affective processes has been recognized in the past few decades. Spinocerebellar ataxias (SCA) and Friedreich ataxia (FRDA) are rare neurodegenerative diseases of the cerebellum presenting mainly with a progressive loss of gait and limb coordination, dysarthria, and other motor disturbances, but also a range of cognitive and neuropsychiatric symptoms. This narrative review summarizes the current knowledge on neuropsychiatric impairment in SCA and FRDA. We discuss the prevalence, clinical features and treatment approaches in the most commonly reported domains of depression, anxiety, apathy, agitation and impulse dyscontrol, and psychosis. Since these symptoms have a considerable impact on patients' quality of life, we argue that further research is mandated to improve the detection and treatment options of neuropsychiatric co-morbidities in ataxia patients.
Keywords: Friedreichova ataxie; Cerebellum; mozeček; komorbidita; Depression; Friedreich ataxia; kvalita života; Spinocerebellar ataxia; Spinocerebellar Ataxias; Neuropsychiatric symptoms; Psychosis; Humans; Comorbidity; Anxiety; Friedreich Ataxia; Apathy; spinocerebelární ataxie; Quality of Life; lidé; Agitation